Estimation of genetic parameters and variability of various cayenne peppers under net shading - GRETTY FEBRIOLA SIAHAAN; MUHAMMAD ACHMAD CHOZIN; MUHAMAD SYUKUR; ARYA WIDURA RITONGA (Society for Indonesian Biodiversity, 2023)
Abstract. Siahaan GF, Chozin MA, Syukur M, Ritonga AW. 2023. Estimation of genetic parameters and variability of various cayenne peppers under net shading. Biodiversitas 24: 5912-5919. The intercropping systems are important concerning the decreasing agricultural land and the increasing population. Chili could be planted as intercrops, but not all chili genotypes were adapted to low light-intensity stress. This study aims to determine the genetic diversity of cayenne pepper under 50% plastic net shade conditions based on morphological and agronomic traits. The study was conducted at the Cikabayan Experimental Field, Institut Pertanian Bogor, Dramaga, Bogor, from January to July 2021. The genetic material consisted of ten genotypes of cayenne pepper from Capsicum annuum L. and ten from Capsicum frustescens L.. Each genotype of chili was planted with three replications, so there were 60 experimental units. Each experimental unit consisted of six plants planted in an area of 1.5 m2. The shade used was a plastic net shade with a 50% shading level. The estimation of genetic parameters showed that leaf area, number of leaves, fruit weight, number of fruits, and yield per plant had a high genotypic coefficient of variation (GCV) and broad-sense heritability (Hbs). Cluster analysis resulted in two main clusters based on twelve chili growth and agronomic characters. All chili genotypes included in Cluster 1 were C. annuum chilies. On the other hand, all the chili genotypes in Cluster 2 were C. frutescens chilies except for the G19 genotype. Cayenne pepper in Cluster 2 had a higher number of leaves, plant height, stem diameter, leaf area, fruit diameter, pedicle length, fruit weight, number of fruits, and yield per plant than cayenne pepper in Cluster 1. The result of this study indicates that C. frutescens cayenne pepper has more potential to be planted under shading conditions and used in intercropping than C. annuum.